2018
DOI: 10.3389/fped.2018.00079
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation of Ventricular Function—For the Neonatologist and Pediatric Intensivist

Abstract: In the neonatal and pediatric intensive care setting, bedside cardiac ultrasound is often used to assess ventricular dimensions and function. Depending upon the underlying disease process, it is necessary to be able to evaluate the systolic and diastolic function of left and or right ventricles. The systolic function of left ventricle is mostly assessed qualitatively on visual inspection “eye-balling” and quantitatively by measuring circumferential fraction shortening or calculating the ejection fraction by Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
102
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 51 publications
1
102
1
3
Order By: Relevance
“…19,20 The echocardiography type referred to as critical-care echocardiography has become a part of the routine evaluation of patients in the PICU by pediatric intensivists. 20,21 This noninvasive technique allows the intensivist to measure ejection fraction, cardiac output and cardiac index and to assess pericardial effusion and becomes a guide for the management of treatment and ensuring the hemodynamic stability of critically ill patients. 21 The importance of cardiac index in guiding fluid and inotropic management in septic shock was emphasized in the recent clinical practice parameters published in 2017, which highlighted the significance of cardiac index measurement in the PICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 The echocardiography type referred to as critical-care echocardiography has become a part of the routine evaluation of patients in the PICU by pediatric intensivists. 20,21 This noninvasive technique allows the intensivist to measure ejection fraction, cardiac output and cardiac index and to assess pericardial effusion and becomes a guide for the management of treatment and ensuring the hemodynamic stability of critically ill patients. 21 The importance of cardiac index in guiding fluid and inotropic management in septic shock was emphasized in the recent clinical practice parameters published in 2017, which highlighted the significance of cardiac index measurement in the PICU.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 This noninvasive technique allows the intensivist to measure ejection fraction, cardiac output and cardiac index and to assess pericardial effusion and becomes a guide for the management of treatment and ensuring the hemodynamic stability of critically ill patients. 21 The importance of cardiac index in guiding fluid and inotropic management in septic shock was emphasized in the recent clinical practice parameters published in 2017, which highlighted the significance of cardiac index measurement in the PICU. 22 In another survey similar to our study, the results showed a 72.7% rate of POCUS use for the assessment of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is becoming a standard of care in many intensive care units and more clinicians are learning how to perform bedside critical care echocardiography technique as more pediatric intensivist are becoming familiar with bedside ultrasonography in the PICU. The echocardiography type referred to as criticalcare echocardiography has become a part of the routine evaluation of patients in the PICU by the pediatric intensivist [8]. This noninvasive technique allows the intensivist to measure and remeasure both CO and CI to guide patient management and ensure maintain hemodynamic stability to a critically ill patient.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac ultrasound, in combination with clinical examination, is more sensitive for detection of cardiovascular compromise compared with clinical examination alone 3,4 . Ejection fraction (EF) is recommended as one of the echocardiographic parameters for detection of left ventricular (LV) systolic dysfunction in neonates 5,6 . LVEF is the fractional difference between left ventricular end‐diastolic volume (LV EDV) and end‐systolic volume (LV ESV) during one cardiac cycle and represents the efficiency of LV pump in handling LV preload and afterload through a dynamic interaction between the ventricle and the arterial system.…”
Section: Introductionmentioning
confidence: 99%